Cutaneous Toxicity Associated With Enfortumab Vedotin: A Real-Word Study Leveraging U.S. Food and Drug Administration Adverse Event Reporting System - Yang, Hui; Yu, Xiaojia; An, Zhuoling (Frontiers in Oncology, 2022)
Introduction Enfortumab vedotin (EV) has been demonstrated to have a significant response rate in early phase trials and is known for its tolerable side-effect profile. Emerging case reports have raised awareness of cutaneous toxicities, which may be a potentially fatal complication. Objective To assess the potential relevance between EV and cutaneous toxicities reports through data mining of the U.S. Food and Drug Administration (FDA) adverse event reporting system (FAERS). Methods Data from January 1, 2019, to November 4, 2021, in the FAERS database were retrieved. Information component (IC) and reporting odds ratio (ROR) were used to evaluate the association between EV and cutaneous toxicities events. Results EV was significantly associated with cutaneous toxicities in the database compared with both all other drugs (ROR 12.90 [10.62–15.66], IC 2.76 [2.52–3.01], middle signal) and platinum-based therapy (ROR 15.11 [12.43–18.37], IC 2.91 [2.66–3.15], middle signal) in the FAERS database. A significant association was detected between EV and all the cutaneous adverse effects (AEs) except erythema, palmar–plantar erythrodysesthesia syndrome, and dermatitis allergic. Both Stevens–Johnson syndrome and toxic epidermal necrolysis occurred 15 times as frequently for EV compared with all other drugs (ROR = 15.20; ROR = 15.52), while Stevens–Johnson syndrome occurred 18 times and toxic epidermal necrolysis occurred 7 times as frequently for EV compared with platinum-based therapy in the database (ROR = 18.74; ROR = 7.80). All groups that limited the gender and age showed a significant association between EV and cutaneous toxicities. Conclusions A significant signal was detected between EV use and cutaneous toxicities. It is worth noting that Stevens–Johnson syndrome and toxic epidermal necrolysis were significantly associated with EV use.